Implementasi Data Warehouse Pada Toko KC Boutique - Crecia Crecia; Michael Junius Aguswan; Andri Wijaya (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2023)
Clothing needs are the main thing that must be met. One of them is KC Boutique. This shop sells various women's clothing and is located in West Jakarta. The aim of this research is to create a Data Warehouse because the KC boutique shop still uses the Excel application to input data. This makes it difficult for owners to combine all the data they have. Therefore ETL is the solution to this problem. Where ETL will integrate all databases in a Data Warehouse which, if connected the data will also continue to be automatically updated. Data collection methods are observation and interviews. The method used is the OLAP method with the process namely ETL. The tool used is SQL Server Management Studio. The result of this research is the design of a Data Warehouse that is connected to the KC Boutique store database so that the data is well integrated.